Maine’s State Parks: Their Value to Visitors and Contribution to the State Economy - Roper, Robert; Morris, Charles; Allen, Thomas; Bastey, Cindy (Maine Policy Review, 2006)
Maine’s state parks are important to the social and economic well-being of the state, and provide public access to a variety of outdoor activities. In the study reported here, the authors find that visitors have a high level of satisfaction in Maine’s day-use parks, campgrounds and historic sites. Moreover, the overall impact of visitor-related park spending exceeds 30 million in income and 1,449 jobs annually. Nonetheless, the majority of Maine’s state parks suffer from long-deferred maintenance and are in immediate need of major capital improvements if they are to continue their vital role in supporting tourism and outdoor recreation.